Implementasi Computational Thinking dalam Pembelajaran Sekolah Dasar: Sebuah Systematic Literature Review terhadap Penelitian Tahun 2021–2026 - M. Gunawan Supiarmo; Gilang Primajati (Mandalika Mathematics and Educations Journal, 2026)
Computational Thinking (CT) is a crucial 21st-century competency that should be cultivated starting at the primary school level. This study aims to analyze research trends, implementation, and the impact of CT in primary school education during the 2021–2026 period. A Systematic Literature Review (SLR) methodology was employed. Scholarly articles were sourced from Scopus, ERIC, SpringerLink, ScienceDirect, ProQuest, SINTA, Garuda, and Google Scholar, and subsequently analyzed using a descriptive-qualitative approach. The findings indicate a rise in CT research, accompanied by increasingly diverse implementation methods-such as Scratch, robotics, STEM, Project-Based Learning, educational games, Artificial Intelligence, and unplugged activities. CT implementation has been shown to enhance algorithmic thinking, decomposition, pattern recognition, abstraction, problem-solving, creativity, and student learning motivation. However, implementation still faces challenges regarding teacher competence, curriculum integration, and the development of appropriate assessments. Consequently, there is a need to strengthen teacher capacity, develop an integrated curriculum, and conduct further research to optimize CT implementation at the primary school level.